Biophysical indicators based on spatial hierarchy for informing land reclamation: The case of the Lower Athabasca River (Alberta, Canada). (January 2017) - Thiffault, Evelyne; Webster, Kara; Lafleur, Benoit; Wilson, Stephanie; Mansuy, Nicolas
Highlights: Biophysical indicators are developed for land reclamation. We create a typology of assemblages at the watershed, landform and ecosite scales. Despite subtle topography, distinct classes of biophysical features are delineated. Reclamation targets need to be based on quantitative hierarchical indicators. Abstract: In the Lower Athabasca region of Alberta (Canada), surface mining for bitumen from oil sands creates highly disturbed environments, which need to be restored, after mine closing, to equivalent land capability in terms of biodiversity and ecosystem services. We demonstrate a method to characterize ecosystem diversity and conditions using biophysical indicators of the Lower Athabasca meant for informing land reclamation planning and monitoring by identifying and creating a typology of the main assemblages of topography, soil and forest vegetation at the watershed, landform and ecosite scales, and analysing the relationships among land units of various scales. Our results showed that watersheds could be classified into distinct groups with specific features, even for a region with a generally flat or gently rolling topography, with slope, surficial deposits and aspect as key drivers of differences. Despite the subtle topography, the moisture regime, which is linked to large-scale cycles that are dependent on the surrounding matrix, was of primary importance for driving vegetation assemblages. There was no unique and homogeneous association between topography and vegetation; the specific landforms each displayed a range of ecosites, and the same ecosites were found in different landforms. This suggests that landscapes cannot be defined in a qualitative manner but rather with quantitative indicators that express the proportion occupied by each class of ecological units within the coarser units, therefore requiring during land reclamation that sufficient care is given to create heterogeneity within a given landform in terms of soil texture and drainage so that a mosaic of ecosite conditions is created.